(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This article presents an experience report developed as part of the university extension project “Awakening the Amazon Biome through the Five Senses,” which fosters dialogue between science, culture, and the school community. The activities took place in public schools in the city of Boa Vista, state of Roraima, through Geology and Anthropology exhibitions aimed at elementary and high school students. The project sought to integrate academic knowledge and local wisdom through participatory methodologies, the use of symbolic elements, and sensory experiences. The results reveal a strengthened sense of belonging among students to the Amazon territory, sparking scientific curiosity and recognition of local ethnic and cultural diversity. The experience reaffirms the transformative role of university extension in promoting meaningful learning and valuing regional knowledge.